Cu-Cr-Nb-Re alloy, preparation method and engine
Through the preparation method of Cu-Cr-Nb-Re alloy, the problems of fatigue and insufficient high-temperature resistance of existing alloys under high temperature and repeated thermal cycling conditions are solved, and higher mechanical properties and lower resource consumption and cost are achieved.
Patent Information
- Application Number
- CN202411900865.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing chromium bronze and chromium zirconium copper alloys have poor fatigue and high temperature resistance under high temperature and repeated thermal cycle conditions, and the production process has problems such as large resource consumption, high cost, low accuracy and long manufacturing cycle.
The preparation method of Cu-Cr-Nb-Re alloy is adopted to form copper liquid by induction melting, niobium and copper-chromium intermediate alloys are added, rare earth elements are added after refining, and casting is used to protect the casting with inert gas to form Cu-Cr-Nb-Re alloy casting rod blanks. Then it is melted and atomized into solution droplets under vacuum, cooled and solidified into powder, and isostatically pressed and spin-pressed, and finally annealed.
It significantly improves the high temperature resistance and high temperature stability of Cu-Cr-Nb-Re alloy, enhances the mechanical properties of the engine thrust chamber interior wall, improves the utilization rate of the alloy, reduces resource consumption and cost, and reduces the complexity and cycle of manufacturing.
Smart Images

Figure CN119710333A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of alloy preparation, and specifically relates to a Cu-Cr-Nb-Re alloy, a preparation method and an engine. Background Art
[0002] The thrust chamber of a liquid rocket engine is an important device of the engine, and the inner wall of the thrust chamber is an important component of the thrust chamber of a rocket engine. The high-temperature, high-pressure gas heat energy generated by the combustion of the propellant is converted into kinetic energy in the thrust chamber. The material of the inner wall of the thrust chamber is required to have good high-temperature resistance and thermal conductivity to conduct away the heat of fuel combustion during the rocket launch to ensure the normal operation of the engine. Chromium bronze and chromium-zirconium-copper alloys have become one of the commonly used materials for the inner wall of the thrust chamber of liquid rocket engines in downstream applications because of their high-temperature stability, heat resistance and superior material thermal conductivity. However, to meet the needs of high thrust and repeated use, it is necessary to further develop materials with better high-temperature performance and fatigue performance.
[0003] The materials currently used for the inner wall of the thrust chamber are mainly chrome bronze and chrome zirconium copper, and the production process is: raw material smelting - forging - solution aging heat treatment - machining. The raw material ingot is obtained by induction melting, the ingot is forged to obtain the inner wall blank, and the forged blank is heat treated and machined to obtain the inner wall finished product. However, the chrome bronze and chrome zirconium copper prepared based on the above production process have poor fatigue performance and high temperature resistance after repeated thermal cycles, and have defects such as large resource consumption, high cost, low precision and long manufacturing cycle. Summary of the invention
[0004] The main purpose of the present application is to provide a Cu-Cr-Nb-Re alloy, a preparation method and an engine. The present application can significantly improve the high temperature resistance and high temperature stability of the Cu-Cr-Nb-Re alloy, thereby enhancing the mechanical properties of the inner wall of the engine thrust chamber.
[0005] A preparation method of a Cu-Cr-Nb-Re alloy, the method comprising: firstly smelting an electrolytic copper plate, after the electrolytic copper plate is melted to form a copper liquid, then adding niobium and a copper-chromium master alloy, after the metal niobium and the copper-chromium master alloy are melted, obtaining a metal mixed solution, continuing to add rare earth elements, and simultaneously using an inert gas for protective casting to form a Cu-Cr-Nb-Re alloy cast rod blank; melting the Cu-Cr-Nb-Re alloy cast rod blank in a vacuum environment to form a Cu-Cr-Nb-Re alloy solution, using an inert gas as an atomizing medium, The Cu-Cr-Nb-Re alloy solution is crushed to form solution droplets, and after the solution droplets are cooled and solidified, Cu-Cr-Nb-Re alloy powder is formed; the Cu-Cr-Nb-Re alloy powder is hot isostatically pressed to obtain a Cu-Cr-Nb-Re alloy flat billet; the Cu-Cr-Nb-Re alloy flat billet is spin-formed to obtain a Cu-Cr-Nb-Re alloy spin-formed billet; the Cu-Cr-Nb-Re alloy spin-formed billet is annealed to obtain a Cu-Cr-Nb-Re alloy.
[0006] Optionally, after obtaining the metal mixed solution, the metal mixed solution needs to be refined.
[0007] Optionally, the rare earth element includes any one of the following combinations: cerium and yttrium, lanthanum and neodymium, cerium, neodymium and yttrium.
[0008] Optionally, after obtaining the Cu—Cr—Nb—Re alloy solution droplets, the Cu—Cr—Nb—Re alloy solution droplets need to be rapidly cooled.
[0009] Optionally, the Cu—Cr—Nb—Re alloy powder is hot isostatically pressed at a temperature of 900° C. to 1000° C., a pressure of 90 MPa to 150 MPa, and a time of 2 h to 4 h.
[0010] Optionally, during the spinning process of the Cu—Cr—Nb—Re alloy flat sheet, the thinning rate needs to be controlled within a range of 0.1% to 0.7%.
[0011] Optionally, during the spinning process of the Cu—Cr—Nb—Re alloy flat sheet, the heating temperature is 500° C. to 700° C.
[0012] Optionally, the annealing temperature of the Cu—Cr—Nb—Re alloy spinning blank is 500°C to 800°C.
[0013] In addition, the present application also provides a Cu-Cr-Nb-Re alloy, the components of which include: chromium (Cr), niobium (Nb), rare earth elements (Re) and copper (Cu), wherein the mass percentages of the chromium (Cr), niobium (Nb), rare earth elements (Re) and copper (Cu) are 2.0wt% to 10.0wt%, 1.0wt% to 5.0wt%, 0.02wt% to 0.10wt%, and the remainder.
[0014] In addition, the present application also provides an engine, wherein the inner wall of the thrust chamber of the engine is made of the Cu-Cr-Nb-Re alloy as described above.
[0015] The present application has the following beneficial effects: the present application can significantly improve the high temperature resistance and high temperature stability of the Cu-Cr-Nb-Re alloy through an innovative Cu-Cr-Nb-Re alloy preparation process, thereby enhancing the mechanical properties of the products prepared based on the alloy. In addition, the present application can greatly improve the utilization rate of the Cu-Cr-Nb-Re alloy, reduce resource consumption and reduce costs, provide a more efficient and reliable solution for the manufacture of the inner wall of the rocket engine thrust chamber, and promote technological progress in the aerospace field. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic flow chart of a method for preparing a Cu-Cr-Nb-Re alloy provided in one embodiment of the present application;
[0017] Figure 2 is a metallographic diagram of a Cu-Cr-Nb-Re alloy prepared by the method described in the present application;
[0018] Figure 3 It is the metallographic diagram of the Cu-Cr-Zr alloy prepared by the existing method. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0021] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0022] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0023] In an exemplary embodiment, the present application provides a Cu-Cr-Nb-Re alloy, wherein the components of the Cu-Cr-Nb-Re alloy include: chromium (Cr), niobium (Nb), rare earth elements (Re) and copper (Cu), wherein the mass percentages of the chromium (Cr), niobium (Nb), rare earth elements (Re) and copper (Cu) are 2.0wt% to 10.0wt%, 1.0wt% to 5.0wt%, 0.02wt% to 0.10wt%, and the remainder.
[0024] In this embodiment, the above ratios are the best ratios obtained by the present application through a series of experimental studies, including smelting, casting, heat treatment and other process steps, preparing alloy samples with different component ratios, and testing the mechanical properties, thermal properties and microstructure of the alloy samples.
[0025] Chromium (Cr) can not only improve the high temperature strength, oxidation resistance and corrosion resistance of the alloy, but also enhance the wear resistance and fatigue resistance of the alloy. Setting the chromium (Cr) content in the range of 2.0wt% to 10.0wt% can effectively improve the hardness and strength of the alloy while maintaining good ductility and toughness. If the content is too low, it will not provide sufficient strengthening effect; if it is too high, it may cause the material to become more brittle and affect its processing performance.
[0026] Niobium (Nb) is a strong carbide-forming element that can significantly improve the high-temperature strength and creep resistance of materials. In addition, it can refine grains and improve the microstructure of materials. Setting niobium (Nb) in the range of 1.0wt% to 5.0wt% can promote the formation of fine and evenly distributed strengthening phases, thereby improving the high-temperature stability and mechanical properties of materials. If the content is too low, the strengthening effect is not obvious; if the content is too high, it may cause excessive hardening of the alloy, which is not conducive to subsequent processing.
[0027] Rare earth elements (Re) can not only refine grains, enhance oxidation resistance, and provide high-temperature strength, but also reduce defects inside the alloy and improve the overall performance of the alloy. Rare earth elements have high chemical activity. Setting rare earth elements (Re) in the range of 0.02wt% to 0.10wt% can give full play to their role in improving alloy performance, such as refining grains, enhancing oxidation resistance and providing high-temperature strength. If the addition amount is too small, the above effects are not significant. If the addition amount is too large, it may lead to increased costs and may cause other adverse effects, such as element segregation.
[0028] Copper (Cu) as the matrix material provides good thermal conductivity and ductility, ensuring the basic physical properties of the alloy. Copper (Cu) as the main component occupies most of the mass percentage of the alloy, which can ensure that the alloy has excellent electrical and thermal conductivity.
[0029] Figure 1 FIG. 1 is a schematic flow diagram of a method for preparing a Cu-Cr-Nb-Re alloy according to an embodiment of the present application, such as Figure 1 As shown, the preparation method comprises:
[0030] S1: firstly add an electrolytic copper plate into an induction melting furnace for smelting, wait for the electrolytic copper plate to melt to form a copper liquid, then add metal niobium (Nb) and copper-chromium (Cu-Cr) master alloy, wait for the metal niobium (Nb) and copper-chromium (Cu-Cr) master alloy to melt, obtain a metal mixed solution, refine the metal mixed solution for 10 minutes, and after the refining is completed, add rare earth elements cerium (Ce) and yttrium (Y) at the same time, and use argon gas for protective casting to form a Cu-Cr-Nb-Ce-Y alloy cast rod blank;
[0031] In this step, the melting point of electrolytic copper is about 1085°C, while the melting point of niobium (Nb) is as high as 2468°C. In contrast, the melting point of the copper-chromium master alloy is between the two. If you try to melt all the metal components at the same time, some elements will evaporate prematurely or melt incompletely due to improper temperature control. By melting the electrolytic copper with a lower melting point first, the temperature can be gradually increased to ensure that the high-melting point materials added later can be melted smoothly. In addition, melting the electrolytic copper to form a liquid base first can provide a more stable melt environment for the subsequent addition of niobium and copper-chromium master alloys, which will help the newly added components to be more evenly dispersed throughout the melt and avoid problems with local excessive concentration or uneven distribution.
[0032] After all components are melted in the present application, the metal mixed solution needs to be refined. By refining the metal mixed solution, all elements can be fully mixed to form a melt with uniform composition. At the same time, gases such as hydrogen and oxygen and defects such as non-metallic inclusions that may exist in the melt can be effectively removed (if these defects remain in the melt, they will form crack sources or other forms of microstructural discontinuities in subsequent processing).
[0033] In addition, the rare earth elements cerium (Ce) and yttrium (Y) are added after refining. After inspection, such an addition step can ensure that the rare earth elements can be evenly distributed in the alloy, which helps to maximize the effect of rare earth elements on improving the performance of the alloy, such as grain refinement, enhanced oxidation resistance and high temperature strength. On the contrary, if the rare earth element cerium is added before or during refining, the rare earth elements cannot be evenly dispersed in the entire alloy melt because the melt has not been fully mixed or is undergoing composition adjustment and purification, resulting in excessively high or low concentrations of rare earth elements in local areas of the alloy melt, thereby affecting the performance consistency of the final alloy. In addition, since rare earth elements such as cerium (Ce) and yttrium (Y) have high chemical activity, they are easy to react with oxygen or other elements in the melt at high temperatures to form compounds such as oxides, and may even partially volatilize. If added before or during refining, these reactions will be more intense, resulting in a decrease in the effective utilization rate of rare earth elements, thereby increasing costs and reducing their effect on improving alloy properties. Furthermore, the refining process aims to remove gases, non-metallic inclusions and other impurities in the melt. If rare earth elements are added before or during this stage, they may react with the impurities in the melt to form new inclusions or difficult-to-remove composite phases, which is not only not conducive to improving the purity of the alloy, but may also become a weak point inside the alloy, thereby affecting the mechanical properties of the alloy.
[0034] It should be noted that one of the contributions of this application to the prior art is that two rare earth elements are added simultaneously during the alloy preparation process (existing processes often only add one rare earth element). Take the rare earth elements yttrium (Y) and cerium (Ce) as examples, where yttrium (Y) can provide excellent high temperature strength and creep resistance, helping to maintain the structural stability and mechanical properties of the alloy at high temperatures; while cerium (Ce) can refine the grains and enhance oxidation resistance, and the fine grains can improve the strength, toughness and thermal conductivity of the alloy, thereby reducing the aging and corrosion risks of the alloy in high temperature environments. When yttrium (Y) and cerium (Ce) are used in combination, the overall performance of the alloy can be optimized in different aspects at the same time. On the contrary, if a rare earth element is added alone, the material properties can only be improved in certain specific aspects, but the overall optimization effect cannot be achieved. For example, adding only yttrium may improve the high temperature strength, but without the contribution of cerium to grain refinement and oxidation resistance, the alloy may still be susceptible to oxidation or exhibit lower toughness.
[0035] It should also be noted that in the process of alloy preparation, testing multiple rare earth element combinations at the same time will increase the complexity of the experiment. Based on existing experience and traditional practices, technicians in this field often believe that adding a single rare earth element can achieve specific functions. Therefore, a tendency has been formed, that is, a single rare earth element is sufficient to meet the preparation requirements of alloys, while ignoring the possibility of multiple element combinations. This application breaks this traditional concept and introduces an innovative way of thinking. Through in-depth research and bold attempts, this application reveals the synergistic effect brought about by the combination of multiple rare earth elements, which is an area that the prior art has not touched.
[0036] S2: placing the Cu-Cr-Nb-Ce-Y alloy cast rod billet into a vacuum induction melting furnace for melting, completely melting the Cu-Cr-Nb-Re alloy cast rod billet under a vacuum environment (the Cu-Cr-Nb-Ce-Y alloy cast rod billet can be prevented from being oxidized under a vacuum environment to ensure the purity of the Cu-Cr-Nb-Re alloy cast rod billet) to form a Cu-Cr-Nb-Ce-Y alloy solution, using an inert gas (such as argon) as an atomizing medium to crush the Cu-Cr-Nb-Ce-Y alloy solution to form tiny Cu-Cr-Nb-Ce-Y alloy solution droplets, and forming Cu-Cr-Nb-Ce-Y alloy powder after the droplets are cooled and solidified;
[0037] In this step, the Cu-Cr-Nb-Ce-Y alloy solution droplets need to be quickly cooled, the temperature of the inert gas is set to minus 10°C to minus 20°C (the low temperature setting can quickly take away the heat and ensure that the droplets complete the transition from liquid to solid in a very short time. Compared with normal temperature or high temperature gas, low temperature inert gas can provide more efficient heat conduction, making the cooling process more uniform and rapid), the gas pressure is set to 2MPa to 5MPa (higher pressure helps to increase the collision frequency between gas molecules and the droplet surface, further accelerating the heat exchange rate. In addition, high pressure conditions can also prevent unnecessary deformation or rupture of the droplets during the cooling process, ensuring the morphological integrity of the powder particles), and the cooling rate is set to 10 3 K / s~10 4 K / s (this cooling rate is much higher than the cooling rate in traditional processes, and can reduce the temperature of the droplets suddenly in a very short time, thereby forming a fine and evenly distributed strengthening phase structure. Such a high cooling rate can effectively inhibit the formation of large-sized grains and promote the precipitation of non-equilibrium phases. These non-equilibrium phases usually have higher hardness and strength, significantly improving the comprehensive mechanical properties of the powder material).
[0038] In summary, traditional cooling methods are often limited by cooling speed and uniformity, making it difficult to achieve such fine microstructure control. However, by setting an ultra-high cooling speed, the atoms inside the droplets do not have enough time to rearrange into an orderly large grain structure, but instead form a large number of finely dispersed strengthening phases. These fine strengthening phases not only enhance the hardness and wear resistance of the material, but also improve the toughness and ductility of the alloy to a certain extent, making it more suitable for the manufacture of complex-shaped parts.
[0039] S3: hot isostatically pressing the Cu-Cr-Nb-Ce-Y alloy powder at a temperature of 900° C. and a hot isostatic pressure of 90 MPa for 2 h to obtain a Cu-Cr-Nb-Ce-Y alloy flat sheet;
[0040] In this step, it has been experimentally verified that the heating temperature of 900°C is the minimum effective temperature for preparing the Cu-Cr-Nb-Ce-Y alloy flat blank. This temperature is sufficient to activate the diffusion process of the metal atoms in the Cu-Cr-Nb-Ce-Y alloy powder, which helps the Cu-Cr-Nb-Ce-Y alloy powder to form a dense and uniform microstructure, thereby improving the overall mechanical properties of the alloy. In addition, the heat generated by this temperature can promote an effective sintering reaction between the powder particles, that is, to reduce the porosity and enhance the bonding force between the particles through solid phase sintering, liquid phase sintering or a combination of the two. If the temperature is lower than 900°C, the sintering process will not be thorough enough, the bonding between the powder particles will not be sufficient, and more pores or tiny defects will be left, thereby increasing the density of the alloy, thereby weakening its mechanical properties including tensile strength and fatigue life. In addition, when the temperature is too low, the Cu-Cr-Nb-Ce-Y alloy powder is difficult to achieve the ideal atomic mobility and cannot form a dense and uniform microstructure. It is very likely to generate larger grains or irregularly distributed second phases, thereby affecting the toughness and ductility of the alloy material.
[0041] In addition, it has been experimentally verified that the hot isobaric pressure of 90 MPa is also the minimum effective pressure for preparing the Cu-Cr-Nb-Ce-Y alloy flat blank, which is sufficient to close the gaps between the Cu-Cr-Nb-Ce-Y alloy powder particles and tightly combine the particles, thereby achieving high densification of the Cu-Cr-Nb-Ce-Y alloy powder. If the pressure is too small (less than 90 MPa), it is not enough to completely eliminate the gaps between the powder particles, resulting in more pores remaining in the Cu-Cr-Nb-Ce-Y alloy flat blank and inconsistent grain sizes, thereby significantly reducing the strength and durability of the Cu-Cr-Nb-Ce-Y alloy flat blank.
[0042] Furthermore, the 2h holding time is sufficient to give the atoms in the Cu-Cr-Nb-Ce-Y alloy powder enough time to diffuse and rearrange, so that the contact points between the powder particles are completely fused to form a continuous matrix. If the time is too short (less than 2h), it is not enough for the atoms to fully diffuse and rearrange, so that the bonding between the powder particles is not strong enough, resulting in more weak connection points inside the powder, which in turn affects the mechanical strength of the final alloy.
[0043] S4: The Cu-Cr-Nb-Ce-Y alloy flat sheet is fixed on a spinning machine, and the spinning machine is started to spin the Cu-Cr-Nb-Ce-Y alloy flat sheet into a semi-conical shape. During the spinning process, the thinning rate is controlled at 0.1%-0.7% (i.e., the thickness reduction ratio of the sheet does not exceed this range during each spinning process). After the Cu-Cr-Nb-Ce-Y alloy flat sheet is initially spun into a plate cone, the sheet is spun into shape using a core mold, and 2 to 4 spinning passes are performed. One-step processing of the blank (using 2 to 4 spinning passes to gradually form a complex shape and reduce the risk of defects caused by a single large deformation), during the spinning process, the heating temperature of the Cu-Cr-Nb-Ce-Y alloy flat blank is set to 500° C., the heating time is set to 20 min, and after the spinning is completed and naturally cooled, the spun Cu-Cr-Nb-Ce-Y alloy flat blank is unloaded from the spinning machine to obtain a Cu-Cr-Nb-Ce-Y alloy spinning blank;
[0044] In this step, the reason why the thinning rate needs to be controlled within 0.1% to 0.7% during the spinning process is that the thinning rate within this range helps to maintain the consistency of the material thickness and can prevent the occurrence of local over-thinning or over-thickness. In addition, the thinning rate within this range can also avoid excessive internal stress caused by rapid deformation. High internal stress will cause cracks or other defects to form inside the material, thereby affecting the quality and reliability of the finished product. If the thinning rate is too large (more than 0.7%), the fine and uniform microstructure inside the material will be destroyed, resulting in elongated grains or irregular distribution, thereby weakening the key properties of the material such as strength, toughness and thermal conductivity. If the thinning rate is too small (less than 0.1%), the residual stress in the Cu-Cr-Nb-Ce-Y alloy flat blank cannot be effectively eliminated, which will affect the quality of the final product.
[0045] In addition, the heating temperature of the Cu-Cr-Nb-Ce-Y alloy flat blank is set to 700°C, and the heating time is set to 20min, which is also verified by experiments. 700°C is a relatively high temperature, which is enough to make the atoms in the Cu-Cr-Nb-Ce-Y alloy flat blank obtain enough energy to migrate, thereby enhancing the plasticity of the material and facilitating uniform deformation during the spinning process without cracks or other defects. If the temperature is too high (greater than 700°C), it may cause unnecessary phase changes or element volatilization, change the chemical composition and microstructure of the material, and the grains therein may also grow excessively, thereby weakening the strength and toughness of the material. Further, the heating time of 20min is enough for the entire flat blank to achieve a uniform temperature distribution, ensuring that each part can be subjected to spinning processing under the same conditions. If the heating time is less than 20min, the Cu-Cr-Nb-Ce-Y alloy flat blank cannot achieve a uniform temperature distribution, resulting in inconsistent processing performance in different regions. In addition, it will also lead to insufficient stress release, thereby leaving more internal stress, which in turn affects the stability and reliability of the finished product.
[0046] S5: preheating the annealing furnace, then placing the Cu-Cr-Nb-Ce-Y alloy spinning blank into the preheated annealing furnace, raising the furnace temperature to 500°C to anneal the Cu-Cr-Nb-Ce-Y alloy spinning blank, keeping it warm for 1 hour and then slowly cooling it to room temperature to obtain the Cu-Cr-Nb-Ce-Y alloy.
[0047] In this step, during the spinning process, the Cu-Cr-Nb-Ce-Y alloy spinning blank undergoes plastic deformation, resulting in high internal stress and work hardening. The temperature of 500°C is sufficient to allow atoms to obtain sufficient energy to rearrange, thereby reducing these internal stresses and partially restoring the ductility and toughness of the material. In addition, this temperature can promote the recrystallization process, that is, the formation of new grains to replace the old grains that are elongated or deformed due to processing. At this temperature, recrystallization can be effectively started without causing excessive grain growth. If the temperature is too low (less than 500°C), it is not enough to fully activate atomic migration, and the residual stress inside the material cannot be effectively eliminated. The residual internal stress may cause microcracks or other defects in subsequent use, thereby reducing the overall strength and reliability of the material. In addition, too low a temperature will also cause the degree of work hardening to fail to be properly alleviated, so that the ductility and toughness of the material are still limited, affecting its performance under complex load conditions.
[0048] It should be noted that after the annealing treatment is completed, the present application designs a multi-stage cooling method, which specifically includes:
[0049] Phase 1: Initial rapid cooling phase;
[0050] In this stage, the temperature of the Cu-Cr-Nb-Ce-Y alloy spinning blank is rapidly reduced from 500°C to 350°C at a rate of 100°C to 150°C per hour. The main purpose of this stage is to quickly pass through the temperature range that may cause phase change, reduce unnecessary phase change or element volatilization, and thus protect the chemical composition and microstructure of the material.
[0051] Stage 2: Intermediate slow cooling stage;
[0052] The Cu-Cr-Nb-Ce-Y alloy spinning blank is cooled from 350°C to 200°C at a rate of 20°C to 30°C per hour. This stage is a critical stress release period. Through a relatively mild cooling rate, the residual stress inside the material can be effectively reduced and the recrystallization process can be promoted, that is, new grains are formed to replace old grains that are elongated or deformed due to processing, thereby improving the ductility and toughness of the material.
[0053] Stage 3: Final slow cooling stage;
[0054] The Cu-Cr-Nb-Ce-Y alloy spinning blank is cooled from 200°C to room temperature at a rate of 10°C to 15°C per hour. This stage is to ensure that when the material is completely cooled to room temperature, the internal microstructure has reached the most ideal densification and flatness, avoiding any potential thermal stress accumulation and ensuring the consistency and reliability of the finished product.
[0055] In summary, the present application adopts a staged cooling method, firstly, it is possible to optimize the microstructure of the Cu-Cr-Nb-Ce-Y alloy: the cooling rate and temperature range of each stage are accurately calculated to ensure the optimal evolution of the internal microstructure of the material at different temperatures. For example, in the initial rapid cooling stage, the phase change sensitive zone can be quickly passed to avoid unnecessary phase change or element volatilization; in the intermediate slow cooling stage, the gentle cooling rate is conducive to the formation of new grains, improving the ductility and toughness of the material; the final slow cooling stage ensures that when the material is completely cooled to room temperature, the internal microstructure reaches the most ideal densification and flatness. If a single cooling rate (whether fast or slow) is used, it is impossible to take into account the needs of all temperature ranges. For example, too fast cooling may lead to local stress concentration, grain elongation or abnormal growth, and too slow cooling may extend the production cycle and may not effectively promote the recrystallization process. Second, it can reduce the internal stress and defects of the Cu-Cr-Nb-Ce-Y alloy: in the slow cooling stage from 350°C to 200°C, the internal stress of the Cu-Cr-Nb-Ce-Y alloy spinning blank is fully released, reducing the high internal stress and crack risk caused by rapid cooling. In addition, the slight vibration treatment further eliminates the residual stress and improves the overall performance of the material. This gradual stress release method makes the finished product more stable and reliable. The use of single-speed cooling is prone to residual internal stress, especially in complex-shaped parts. These stresses may become weak points in subsequent use and increase the risk of failure. Third, due to the more uniform microstructure and lower internal stress, the Cu-Cr-Nb-Re alloy after staged cooling can show higher strength, toughness and thermal conductivity, especially after high-temperature cyclic heating, it can still maintain good yield strength, enhancing the long-term reliability of the inner wall of the thrust chamber under extreme conditions. The use of a single cooling method may not be able to achieve the same level of mechanical performance optimization, especially in high-temperature environments. The performance may be affected.
[0056] In another exemplary embodiment, the present application also provides a method for preparing a Cu-Cr-Nb-Re alloy, the method comprising the following steps:
[0057] S10: firstly add the electrolytic copper plate into the induction melting furnace for melting, wait for the electrolytic copper plate to melt to form copper liquid, then add metal niobium (Nb) and copper-chromium (Cu-Cr) master alloy, wait for the metal niobium (Nb) and copper-chromium (Cu-Cr) master alloy to melt, obtain a metal mixed solution, refine the metal mixed solution for 25 minutes, and after the refining is completed, add rare earth elements lanthanum (La) and neodymium (Nd) at the same time, and use argon gas for protection casting to form a Cu-Cr-Nb-La-Nd alloy cast rod blank;
[0058] In this step, lanthanum (La) can improve the strength and toughness of the material, while also enhancing its oxidation resistance, thereby improving the material's plastic deformation ability and weldability; neodymium (Nd) can optimize the material's electrical conductivity and thermal conductivity, thereby improving the material's heat dissipation.
[0059] S20: placing the Cu-Cr-Nb-La-Nd alloy cast rod blank into a vacuum induction melting furnace, completely melting the Cu-Cr-Nb-La-Nd alloy cast rod blank under a vacuum environment (to prevent oxidation of the Cu-Cr-Nb-La-Nd alloy cast rod blank so as to ensure the purity of the Cu-Cr-Nb-La-Nd alloy cast rod blank), using an inert gas (such as argon) as an atomizing medium to crush the completely melted Cu-Cr-Nb-La-Nd alloy cast rod blank to form tiny droplets, which are rapidly cooled and solidified to form Cu-Cr-Nb-La-Nd alloy powder;
[0060] S30: hot isostatic pressing the Cu-Cr-Nb-La-Nd alloy powder at a temperature of 950° C. and a hot isostatic pressure of 120 MPa for 3 hours to obtain a Cu-Cr-Nb-La-Nd alloy flat sheet;
[0061] S40: The Cu-Cr-Nb-La-Nd alloy flat sheet blank is fixed on a spinning machine, and the spinning machine is started to spin the Cu-Cr-Nb-La-Nd alloy flat sheet blank into a semi-conical shape. During the spinning process, the thinning rate is controlled at 0.1-0.7%. After the Cu-Cr-Nb-La-Nd alloy flat sheet blank is initially spun into a plate cone, the blank is spun into shape using a core mold, and the blank is further processed through 2 to 4 spinning passes. During the spinning process, the heating temperature of the Cu-Cr-Nb-La-Nd alloy flat sheet blank is 600° C., and the heating time is 35 minutes. After the spinning is completed and naturally cooled, the spun Cu-Cr-Nb-La-Nd alloy flat sheet blank is unloaded from the spinning machine to obtain a Cu-Cr-Nb-La-Nd alloy spun blank;
[0062] S50: preheating the annealing furnace, then placing the Cu-Cr-Nb-La-Nd alloy spinning blank into the preheated annealing furnace, raising the furnace temperature to 650°C to anneal the Cu-Cr-Nb-La-Nd alloy spinning blank, keeping it warm for 2.5 hours and then slowly cooling it to room temperature to obtain a Cu-Cr-Nb-La-Nd alloy.
[0063] In this step, the Cu—Cr—Nb—La—Nd alloy spinning blank after annealing is still cooled in stages as described above, which will not be described again here.
[0064] In another exemplary embodiment, the present application also provides a method for preparing a Cu-Cr-Nb-Re alloy, the method comprising the following steps:
[0065] S100: firstly add an electrolytic copper plate into an induction melting furnace for smelting, and after the electrolytic copper plate is melted to form a copper liquid, add metal niobium (Nb) and a copper-chromium (Cu-Cr) master alloy, and after the metal niobium (Nb) and the copper-chromium (Cu-Cr) master alloy are melted, a refined metal mixed solution is obtained, and the metal mixed solution is refined for 40 minutes. After the refining is completed, rare earth elements cerium (Ce), neodymium (Nd) and yttrium (Y) are added at the same time, and argon is used for protective casting to form a Cu-Cr-Nb-Ce-Nd alloy cast rod blank;
[0066] In this step, the roles of cerium (Ce) and yttrium (Y) have been described in the above embodiments. Neodymium (Nd) can not only significantly improve the electrical conductivity and thermal conductivity of the material, but also help reduce the residual stress inside the alloy and prevent the formation of cracks and other defects, thereby improving the overall stability and reliability of the alloy.
[0067] Compared with the aforementioned embodiments, the combination of three rare earth elements, namely cerium (Ce), neodymium (Nd) and yttrium (Y), can be the most preferred. These three rare earth elements can act synergistically. The combination of cerium (Ce) grain refinement and yttrium (Y) high temperature strength makes the material both strong and ductile, and can maintain structural integrity and mechanical properties under high temperature and high pressure environments. The addition of neodymium ensures that the alloy can maintain efficient heat conduction at high temperatures, quickly remove the heat generated by combustion, and ensure the safe operation of the engine; cerium (Ce) and yttrium (Y) work together to provide excellent antioxidant protection, reduce the possibility of material aging in high temperature and corrosive environments, especially under repeated thermal cycle conditions; cerium (Ce) and neodymium (Nd) can promote the recrystallization and plastic deformation of the material, making the manufacture of complex shapes easier and the finished product quality higher, thereby reducing production costs and improving efficiency.
[0068] In summary, in the application of the inner wall of the thrust chamber of the liquid rocket engine, the combination of cerium (Ce) + neodymium (Nd) + yttrium (Y) can bring comprehensive performance improvements to the material. For example, under high temperature and high pressure working conditions, this combination can ensure that the inner wall of the thrust chamber can not only withstand extremely high temperatures and pressures, but also effectively transfer heat away while maintaining structural integrity and long-term reliability. In addition, due to its good processing performance, complex-shaped parts can be manufactured through precision spinning and other forming processes to meet design requirements and ensure high quality standards.
[0069] S200: placing the Cu-Cr-Nb-Ce-Nd alloy cast rod blank into a vacuum induction melting furnace, completely melting the Cu-Cr-Nb-Ce-Nd alloy cast rod blank under a vacuum environment (to prevent oxidation of the Cu-Cr-Nb-Ce-Nd alloy cast rod blank so as to ensure the purity of the Cu-Cr-Nb-Ce-Nd alloy cast rod blank), using an inert gas (such as argon) as an atomizing medium to crush the completely melted Cu-Cr-Nb-Ce-Nd alloy cast rod blank to form tiny droplets, which are rapidly cooled and solidified to form Cu-Cr-Nb-Ce-Nd alloy powder;
[0070] S300: hot isostatic pressing the Cu-Cr-Nb-Ce-Nd alloy powder at a temperature of 1000° C. and a hot isostatic pressure of 150 MPa for 4 hours to obtain a Cu-Cr-Nb-Ce-Nd alloy flat sheet;
[0071] In this step, it has been experimentally verified that the heating temperature of 1000°C is the maximum effective temperature for preparing Cu-Cr-Nb-Ce-Nd alloy flat blanks. This temperature is a higher temperature point that can be reached without causing excessive changes in the internal structure of the material. It can not only achieve effective sintering but also protect the material from overheating damage. At this temperature, the metal atoms have enough energy to migrate, thereby effectively promoting the sintering process between powder particles, so that the material reaches a high degree of densification. If the temperature is too high (greater than 1000°C), it will cause the grains to grow rapidly to form large-sized grains, thereby destroying the original fine and uniform microstructure, thereby weakening the strength and toughness of the material. In addition, if the temperature is too high, it will also cause some alloy elements to undergo phase change or volatilization, thereby changing the chemical composition and microstructure of the material. For example, niobium (Nb) and other elements may form new unstable phases at extremely high temperatures, or escape from the matrix, which will seriously affect the performance of the material.
[0072] In addition, it has been experimentally verified that the hot isobaric pressure of 150Mpa is also the maximum effective pressure for preparing Cu-Cr-Nb-Ce-Nd alloy flat blanks. Under this pressure, the gaps between the Cu-Cr-Nb-Ce-Nd alloy powder particles can be closed and the particles can be tightly combined, thereby achieving a high degree of densification of the material. If the pressure is too large (greater than 150Mpa), it will cause the material to be over-densified and produce too much residual stress, which is easy to cause microcracks or delamination during the subsequent cooling process, thereby damaging the overall performance of the material. In addition, if the pressure is too large, the material may undergo uneven plastic deformation, especially when there are local weak points, cracks or other defects may be formed, thereby reducing the strength and toughness of the material. Further, excessive pressure may also cause changes in the migration behavior of certain alloying elements under high pressure, causing component segregation, thereby affecting the chemical uniformity of the material and the consistency of the microstructure.
[0073] Furthermore, under the conditions of 1000°C and 150 MPa, 4 h is enough to close the gaps between the powder particles and achieve high densification, thereby improving the density and strength of the material. If the time is too long, it may cause unnecessary microstructural changes, such as excessive grain growth or second phase precipitation, which will have a negative impact on material properties.
[0074] S400: The Cu-Cr-Nb-Ce-Nd alloy flat sheet blank is mounted on a spinning machine and fixed, and the spinning machine is started to spin the Cu-Cr-Nb-Ce-Nd alloy flat sheet blank into a semi-conical shape. During the spinning process, the thinning rate is controlled at 0.1% to 0.7%. After the Cu-Cr-Nb-Ce-Nd alloy flat sheet blank is initially spun into a plate cone, the blank is spun into shape using a core mold, and the blank is further processed through 2 to 4 spinning passes. During the spinning process, the heating temperature of the Cu-Cr-Nb-Ce-Nd alloy flat sheet blank is 700° C., and the heating time is 50 minutes. After the spinning is completed and naturally cooled, the spun Cu-Cr-Nb-Ce-Nd alloy flat sheet blank is unloaded from the spinning machine to obtain a Cu-Cr-Nb-Ce-Nd alloy spun blank.
[0075] S500: preheating the annealing furnace, then placing the Cu-Cr-Nb-Ce-Nd alloy spinning blank into the preheated annealing furnace, raising the furnace temperature to 800°C to anneal the Cu-Cr-Nb-Ce-Nd alloy spinning blank, keeping it warm for 4 hours and then slowly cooling it to room temperature to obtain a Cu-Cr-Nb-Ce-Nd alloy.
[0076] In this step, for the Cu-Cr-Nb-Ce-Nd alloy flat sheet, 800°C can ensure that it is in a suitable heat treatment state, avoiding unnecessary phase changes or element volatilization caused by excessively high temperature, and also preventing the work hardening caused by too low temperature from being fully relieved. In addition, this temperature can also help release the residual stress inside the Cu-Cr-Nb-Ce-Nd alloy flat sheet, reduce the new stress formed during the spinning process, and thus improve the stability and reliability of the finished product. Further, through annealing at 800°C, the crystal defects inside the Cu-Cr-Nb-Ce-Nd alloy flat sheet can be reduced, and its thermal conductivity and high temperature resistance can be improved, thereby enhancing the working ability of the inner wall of the thrust chamber in a high temperature environment. If the temperature is too high (greater than 800°C), first, it may cause the grains to grow rapidly, destroy the original fine and uniform microstructure, and then weaken the strength and toughness of the material; second, it will increase the risk of oxidation on the surface of the material.
[0077] Furthermore, 4 hours is enough for the entire spinning blank to reach a uniform temperature distribution and give the material enough time to complete the necessary physical changes, such as atomic diffusion and stress release, without increasing energy consumption or causing other problems due to excessive time. If the time is too long (greater than 4 hours), it may cause segregation or uneven distribution of components inside the material, thus affecting the mechanical and thermal properties of the final product.
[0078] In summary, the annealing temperature of 800°C and the holding time of 4h are the maximum effective parameter combinations verified by experiments and engineering practice. If these two values exceed the specified range, a series of adverse effects may occur, including but not limited to abnormal grain growth, phase transformation and element volatilization, increased oxidation risk, increased energy consumption and cost, potential microstructural changes, and decreased equipment utilization.
[0079] It should be noted that, in this step, the Cu—Cr—Nb—La—Nd alloy spinning blank after annealing is still cooled in stages as described above, which will not be described again here.
[0080] Figure 2 is a metallographic diagram of a Cu-Cr-Nb-Re alloy prepared by the method described in the present application; Figure 3 It is the metallographic diagram of the Cu-Cr-Zr alloy prepared by the existing method. Figure 2It can be seen that the distribution of the internal constituent phases of the Cu-Cr-Nb-Re alloy material prepared by the method described in the present application is very fine and smooth, without obvious coarse particles or uneven areas. The grain size is small and consistent, indicating that the Cu-Cr-Nb-Re alloy material prepared by the method described in the present application has a finer crystal structure, and the finer crystal structure can more effectively prevent the grain boundary sliding and diffusion process at high temperature, thereby improving the strength and softening resistance of the material in a high temperature environment. Therefore, the inner wall of the thrust chamber made of this new material can maintain structural integrity and mechanical properties at higher temperatures. Figure 2 It can be seen that the Cu-Cr-Nb-Re alloy material prepared by the existing method shows a relatively rough and irregular microstructure, which is usually accompanied by lower yield strength and tensile strength. Especially when undergoing repeated thermal cycles, the material may suffer fatigue damage, further weakening its mechanical properties, which may cause the inner wall of the thrust chamber to deform, crack or even perforate under the action of high-pressure gas, thus seriously affecting the working efficiency and safety of the engine. In addition, Figure 3 There are also larger particles and the distribution between different phases is more disordered, which means that there may be more defects or weak points inside the material. In a high temperature environment, these defects can easily become the starting point for crack propagation, causing the material to soften or fail prematurely. Therefore, the inner wall of the thrust chamber manufactured using traditional methods may not be able to withstand a long-term high-temperature working environment, increasing the risk of failure during rocket launch.
[0081] Next, the present application conducts a performance test comparison between the alloy prepared based on the existing method and the alloy prepared by the present application. The comparison results are shown in Table 1:
[0082] Table 1
[0083]
[0084] In Table 1, the alloy prepared by the existing method begins to soften between 500°C and 550°C, while the softening temperature of the alloy prepared by the method described in the present application is significantly increased to over 700°C. This means that the material prepared by the method described in the present application has better high temperature resistance.
[0085] In addition, the yield strength of the alloy prepared based on the existing method after high temperature treatment is relatively low, ranging from 40Mpa to 80Mpa; while the alloy prepared by the present method can still maintain a relatively high yield strength under the same conditions, greater than 100Mpa, indicating that the alloy prepared based on the method described in this application is more stable and tougher under high temperature and repeated thermal cycles.
[0086] Furthermore, the utilization rate of alloys prepared based on existing methods is very low, only 1% to 5%, which means a large amount of material waste; in contrast, the utilization rate of alloys prepared based on the method described in the present application is greatly improved, reaching 10% to 50%, which not only reduces resource consumption but also reduces costs.
[0087] In summary, the preparation method of a Cu-Cr-Nb-Re alloy provided in the present application is significantly superior to the existing manufacturing process, especially in improving the high temperature resistance, high temperature stability and improving the utilization rate of the alloy.
[0088] In another exemplary embodiment, the present application also provides an engine, wherein the inner wall of the thrust chamber of the engine is made of the Cu-Cr-Nb-Re alloy as described above.
[0089] In this embodiment, the softening temperature of the Cu-Cr-Nb-Re alloy prepared by this method is significantly increased to above 700°C, which means that when the rocket engine is working, the inner wall of its thrust chamber can withstand higher temperatures without softening or deformation, thereby ensuring the stable operation of the engine under extreme conditions. In addition, even after multiple high-temperature cyclic heating at above 900°C, the Cu-Cr-Nb-Re alloy prepared by this method can still maintain a yield strength of more than 100Mpa, which shows that it has excellent mechanical stability under high temperature and repeated thermal cycle conditions, reduces the risk of fatigue damage, and enhances the long-term reliability of the inner wall of the thrust chamber.
[0090] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a Cu-Cr-Nb-Re alloy, characterized in that: The method comprises: First, the electrolytic copper plate is smelted, and after the electrolytic copper plate is melted to form copper liquid, niobium and copper-chromium master alloy are added, and after the metal niobium and copper-chromium master alloy are melted, a metal mixed solution is obtained, and rare earth elements are continuously added. At the same time, inert gas is used for protective casting to form a Cu-Cr-Nb-Re alloy cast rod blank; The Cu-Cr-Nb-Re alloy cast rod blank is melted in a vacuum environment to form a Cu-Cr-Nb-Re alloy solution, an inert gas is used as an atomizing medium to break up the Cu-Cr-Nb-Re alloy solution to form solution droplets, and after the solution droplets are cooled and solidified, a Cu-Cr-Nb-Re alloy powder is formed; Hot isostatic pressing the Cu-Cr-Nb-Re alloy powder to obtain a Cu-Cr-Nb-Re alloy flat sheet; Spinning the Cu-Cr-Nb-Re alloy flat sheet to obtain a Cu-Cr-Nb-Re alloy spun sheet; The Cu-Cr-Nb-Re alloy spinning blank is annealed to obtain a Cu-Cr-Nb-Re alloy.
2. The method for preparing a Cu-Cr-Nb-Re alloy according to claim 1, characterized in that: After obtaining the metal mixed solution, the metal mixed solution needs to be refined.
3. The method for preparing a Cu-Cr-Nb-Re alloy according to claim 1, characterized in that: The rare earth element includes any one of the following combinations: cerium and yttrium, lanthanum and neodymium, cerium, neodymium and yttrium.
4. The method for preparing a Cu-Cr-Nb-Re alloy according to claim 1, characterized in that: After obtaining the Cu—Cr—Nb—Re alloy solution droplets, the Cu—Cr—Nb—Re alloy solution droplets need to be rapidly cooled.
5. The method for preparing a Cu-Cr-Nb-Re alloy according to claim 1, characterized in that: The Cu—Cr—Nb—Re alloy powder is hot isostatically pressed at a temperature of 900° C. to 1000° C., a pressure of 90 MPa to 150 MPa, and a time of 2 h to 4 h.
6. The method for preparing a Cu-Cr-Nb-Re alloy according to claim 1, characterized in that: During the spinning process of the Cu-Cr-Nb-Re alloy flat sheet, the thinning rate needs to be controlled within a range of 0.1% to 0.7%.
7. The method for preparing a Cu-Cr-Nb-Re alloy according to claim 1, characterized in that: During the spinning process of the Cu-Cr-Nb-Re alloy flat sheet, the heating temperature is 500°C to 700°C.
8. The method for preparing a Cu-Cr-Nb-Re alloy according to claim 1, characterized in that: The annealing temperature of the Cu-Cr-Nb-Re alloy spinning blank is 500°C to 800°C.
9. A Cu-Cr-Nb-Re alloy, characterized in that: The components of the Cu-Cr-Nb-Re alloy include: chromium (Cr), niobium (Nb), rare earth elements (Re) and copper (Cu), wherein the mass percentages of the chromium (Cr), niobium (Nb), rare earth elements (Re) and copper (Cu) are 2.0wt% to 10.0wt%, 1.0wt% to 5.0wt%, 0.02wt% to 0.10wt%, and the remainder.
10. An engine, characterized in that: The inner wall of the thrust chamber of the engine is made of the Cu-Cr-Nb-Re alloy described in claim 9.
Citation Information
Cited By
Copper alloy combustion chamber with gradient structure and preparation method thereof
CN120861817A